PRODUKSI KARBONDIOKSIDA (CO,) SEBAGAI INDIKATOR RESPIRASI PADA BERBAGAI SAYURAN - Hutubessy, Josina Irene Brigetha; Tungga, Dionisius (Agriculture Faculty of Flores University, 2009)
The objective of the research was to determine the respiration rate of vegetable through calculating CO, content resulted from the respiration process. The nature of the research was experimental research which held in a laboratory at the Faculty of Agriculture, Flores University. The result showed that respiration process released C02 and energy. Titration result in yam showed higher C02 content in comparison to cabbage and mustard green. However, the respiration rate of mustard green was higher than other vegetables. The logic behind the results was that the position and the number of stomata per area of the leaf determine respiration rate. In this case, the number of stomata on the mustard green was higher than other observed vegetables. In fact, the respiration rate of vegetables is determined by several factors. Specifically, some internal and external factors affect it, such as soluble matters availability, oxygen, temperature, type and development stage of plants. Morphologically, certain vegetables produce more moisture content than others, which is, in turn, produce low respiration rate.